Molecular characterization of cell decay in inflammation and topological assignment of released cfDNA for integrative laboratory and radiological outcome assessment - Gerhards, Catharina; Nittka, Stefanie; Ast, Volker; Evliyaoglu, Osman; Hedtke, Maren; Hench, Jürgen Christian Hans; Gerigk, Marlis; Krebs, Jörg; Teufel, Andreas; Froelich, Matthias F.; Fischer, Andreas; Schönberg, Stefan; et al. (Frontiers in Cellular and Infection Microbiology, 2026)
BackgroundIntegrative biomarkers could aid in the efficient triage of vulnerable patients with systemic infectious diseases. Thus, we investigated cfDNA integrity, cfDNA epigenetics, and radiomics for their potential as prognostic biomarkers for clinical courses in ARDS and systemic involvement.MethodsThe cfDNA integrity index was established using automated gel electrophoresis (TapeStation) based on the release of cfDNA induced by apoptosis and necrosis in HEK293 and Jurkat cells (discovery cohort). This method was then used to evaluate cfDNA fragmentation patterns in blood samples from participants with COVID-19 or other acute diseases (validation cohort). In this analysis, various cfDNA size intervals (50-130 bp, 130-270 bp, 270-450 bp, 450-640 bp, 640-800 bp) were considered, and both the classic DNA integrity index (247/50-800 bp) and an adjusted index (450/50-800 bp) were assessed for their clinical potential in respiratory diseases. Infinium Methylation 850K assay was utilized for topological assignment of secondary organ damage via epigenetic analysis of cfDNA via deconvolution. In total, 122 samples, including cell culture and patient samples, were analysed.ResultsParticipants with ARDS exhibited higher cfDNA concentrations with fragment sizes above 247 bp (p = 0.016). Increased cfDNA fragment sizes were observed in association with ICU admission (p = 0.009) and mortality (p = 0.017). The predominant origin of cfDNA was hematopoietic cells. An elevated epigenetic hepatocyte signal showed a strong correlation with GGT levels (r = 0.79). Hepatocyte-derived cfDNA anticipated later ALT elevation (p = 0.008). ECMO was correlated with selected radiomics parameters (r = -0.84).ConclusionImplementing the cfDNA integrity index on an automated gel electrophoresis demonstrated promising results in predicting clinical outcomes like ARDS occurrence and mortality. Therefore, integrating laboratory and imaging resources could enhance the allocation of optimal care and may identify secondary systemic complications, especially liver involvement, as our results suggest reduced lead-time for detecting liver injury.
Gesehen am 26.02.2026